QUALITATIVE REVIEW OF ANTIBIOTIC USE FOR NEONATAL SEPSIS - Wei, Tjio Ie; Ascobat, Purwantyastuti; Rohsiswatmo, Rinawati; Instiaty, Insti (International Journal of Applied Pharmaceutics, 2018)
Objective: The aim of this study is to evaluate the antibiotic use in neonates with sepsis. Methods: An observational retrospective study was conducted using medical records of neonates diagnosed with early-/late-onset sepsis who were prescribed antibiotics and who were treated in the neonatal intensive care unit (NICU) at the Dr. Cipto Mangunkusumo Hospital between January 1 and December 31, 2015. Patient records were screened for antibiotic use; qualitative analyses were performed using the Gyssens algorithm. Concordance of empirical antibiotic prescriptions with subsequent blood culture and sensitivity tests was evaluated. Results: A total of 176 sepsis cases included 80 and 96 neonates with normal and low birth weights (LBWs), respectively. Ampicillinsulbactam+ gentamycin, which is indicated in local guidelines as the first-line antibiotic combination for neonatal sepsis, was most frequently prescribed. In the normal birth weight group, appropriate antibiotic use (Gyssens Category I) was found in 89.7% of cases, whereas Gyssens Category V (no indication) was found in 4.54% of cases. In the LBW group, 88.1% and 6.2% of cases were included in Gyssens Categories I and V, respectively. Only 17.5% and 13.5% cultured blood specimens from normal and LBW groups, respectively, yielded positive results; the most commonly identified bacteria were Acinetobacter baumannii and Klebsiella pneumonia. All isolates were resistant to ampicillin-sulbactam; only 7.4% were sensitive to gentamicin. Conclusion: Antibiotic use for neonatal sepsis in NICU in this study can be considered appropriate, suggesting proper implementation of antimicrobial guidelines. However, high rates of resistance to the first-line antibiotics for neonatal sepsis are concerning.